2015
DOI: 10.1080/15548627.2015.1040969
|View full text |Cite
|
Sign up to set email alerts
|

Macroautophagy is essential for killing of intracellularBurkholderia pseudomalleiin human neutrophils

Abstract: -associated membrane protein 1; LC3-I, unlipidated form of LC3; LC3-II, LC3-phospholipid conjugated and phagophore or autophagosome-associated form of LC3; MAP1LC3/LC3, microtubule-associated protein 1 light chain 3; MOI, multiplicity of infection; NET, Neutrophil Extracellular Taps; p.i., postinfection; T3SS, Type III secretion system; WT, wild typeNeutrophils play a key role in the control of Burkholderia pseudomallei, the pathogen that causes melioidosis. Here, we show that survival of intracellular B. pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
0
24
1
Order By: Relevance
“…The effects of hypoxia on these neutrophil functions could be beneficial for pathogen clearance, but could be detrimental for tissue injury and the resolution of inflammation . Interestingly, many of the neutrophil functional responses listed above have also been associated with increased autophagy, and our findings suggest that hypoxia‐induced autophagy may play a role in the observed modulation of neutrophil function in inflammation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The effects of hypoxia on these neutrophil functions could be beneficial for pathogen clearance, but could be detrimental for tissue injury and the resolution of inflammation . Interestingly, many of the neutrophil functional responses listed above have also been associated with increased autophagy, and our findings suggest that hypoxia‐induced autophagy may play a role in the observed modulation of neutrophil function in inflammation.…”
Section: Discussionmentioning
confidence: 58%
“…Recent investigations have described the generation of autophagosomes in neutrophils as a process of lysosome and phagosome fusion, involving the activation of transcription factors and signaling proteins such as CREB and TFEB Tollip, IRAK‐M, and SIRT1 . There is accumulating evidence that activation of autophagy assists with neutrophil microbicidal activity and is an integral process in the regulation of neutrophil fate in inflammation . Specifically, autophagy has been proposed to be a protective process that limits neutrophil recruitment and consequent tissue damage and aids the resolution of neutrophil‐mediated inflammation, as demonstrated in ATG5 –/– mice with tuberculosis infection and in cigarette smoke‐exposed neutrophils …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also found that after boosting with specific antigen, human IgG antibody was affinity-matured, implying that antigen-specific memory B cells with higher affinity Figure 6. 64 Moreover, induction of autophagy in neutrophils leads to the formation of neutrophil extracellular traps, 65,66 and both autophagy and neutrophil extracellular traps are important antibacterial mechanisms against B. pseudomallei. Antigen-specific purified pooled human plasma antibodies by affinity chromatography (a) and sera from hu-PBL-SCID mice 14 days after boosting with either PBS (non-boosted), FliC, OmpA and N-PilO2 (b) were used for FITC-labelled opsonization of dead, intact B. pseudomallei.…”
Section: Discussionmentioning
confidence: 99%
“…62,63 Our previous study on primary human neutrophils infected with B. pseudomallei has demonstrated that neutrophils could kill intracellular B. pseudomallei through autophagy. 64 Moreover, induction of autophagy in neutrophils leads to the formation of neutrophil extracellular traps, 65,66 and both autophagy and neutrophil extracellular traps are important antibacterial mechanisms against B. pseudomallei. 67,68 Hence, the enhancement of bacterial uptake and oxidative burst of neutrophils by antibodies against FliC, OmpA and N-PilO2 would be an important mechanism in host defence against B. pseudomallei infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study demonstrated that macroautophagy is essential for killing of intracellular B. pseudomallei in human neutrophils (Rinchai et al, 2015) and we next investigated whether deletion of glbC would affect the intracellular survival ability of the bacteria in human neutrophils. PMNs were isolated and infected with an MOI of 10 for 1, 3 and 6 hr and intracellular bacteria enumerated.…”
Section: A δGlbc Mutant Shows a Growth Defect In Human Neutrophilsmentioning
confidence: 99%